Screening race in American nontheatrical film - Field, Allyson Nadia and Gordon, Marsha (Duke University Press, 2019)
Although overlooked by most narratives of American cinema history, films made for purposes outside of theatrical entertainment dominated twentieth-century motion picture production. This volume adds to the growing study of nontheatrical films by focusing on the ways filmmakers developed and audiences encountered ideas about race, identity, politics, and community outside the borders of theatrical cinema. The contributors to Screening Race in American Nontheatrical Film examine the place and role of race in educational films, home movies, industry and government films, anthropological films, and church films as well as other forms of nontheatrical filmmaking. From filmic depictions of Native Americans and films by 1920s African American religious leaders to a government educational film about the unequal treatment of Latin American immigrants, these films portrayed--for various purposes and intentions--the lives of those who were mostly excluded from the commercial films being produced in Hollywood. This volume is more than an examination of a broad swath of neglected twentieth-century filmmaking; it is a reevaluation of basic assumptions about American film culture and the place of race within it. Contributors. Crystal Mun-hye Baik, Jasmyn R. Castro, Nadine Chan, Mark Garrett Cooper, Dino Everett, Allyson Nadia Field, Walter Forsberg, Joshua Glick, Tanya Goldman, Marsha Gordon, Noelle Griffis, Colin Gunckel, Michelle Kelley, Todd Kushigemachi, Martin L. Johnson, Caitlin McGrath, Elena Rossi-Snook, Laura Isabel Serna, Jacqueline Najuma Stewart, Dan Streible, Lauren Tilton, Noah Tsika, Travis L. Wagner, Colin Williamson
https://katalog.adlr.link/Record/0-1683257685